Behavioral Addiction and Student Well being: Examining the Mental Health Impact of Social Media - Malizal, Zelynda Zeinab (Sinergi International Journal of Psychology, 2025)
Social media has become an integral part of student life, particularly among undergraduates in Southeast Asia. This study investigates the association between the intensity of social media use and mental health outcomes among students at Universitas Muslim Indonesia. A cross sectional design was employed with a sample of 120 students drawn from seven faculties. Data were collected using the Bergen Social Media Addiction Scale (BSMAS) and the General Health Questionnaire 12 (GHQ 12), and analyzed using the Kolmogorov–Smirnov test, Pearson correlation, and linear regression in SPSS version 29. The results revealed a significant positive correlation (r = 0.342, p < 0.001) between social media use intensity and psychological distress. Regression analysis indicated that social media intensity significantly predicted GHQ 12 scores (β = 0.372, p = 0.001), explaining 11.7% of the variance in mental health outcomes. These findings suggest that while social media serves communicative and informational functions, its excessive use may adversely affect students' psychological well being. The study underscores the importance of self regulation, coping strategies, and institutional support in moderating the psychological effects of digital engagement. Interventions promoting digital literacy and adaptive coping should be prioritized in university settings. This research contributes to the global discourse on digital health by contextualizing student mental health within the digital behaviors of non Western academic populations.